Diagramas de perfil e de cobertura de um trecho da floresta de tabuleiro na Reserva Florestal de Linhares (Espírito Santo, Brasil) - Peixoto, Ariane Luna; Rosa, Maria Mercedes Teixeira da; Joels, Luiz Carlos de Miranda (Acta Botanica Brasilica, 1995)
The profile and the cover diagram of a section of the "tabuleiro" forest at the Linhares Forest Reserve, in the State of Espírito Santo, Brazil, were obtained from two samples of 60m x 10m and 30m x 20m, respectively, partially overlapping. All trees in the sample which exceeded 6m high and has 5cm dbh or more were identified and measured for total height, trunk height, dbh and crown diameter. The trunk and the shapes of the crowns were dravvn. The trees were classified according to their developmental degree into potential trees, present trees end decrepit trees. Three strata were found with distint dimensional, taxonomic and developmental features. Structural characteristic of the succeeding vegetation are related to the vvay trees in the upper stratum die, standing or falling.
Profile and cover diagram of a section of the "tabuleiro" forest at the Linhares Forest Reserve; [Espírito Santo, Brasil]
Keywords: Hiléia Bahiana; Forest Stratification; Profile, Diagram; Atlantic Forest; Hiléia Bahiana; Estratificação Florestal; Diagramas De Perfil E Cobertura; Floresta Atlântica